Attitudes of nurses towards the use of physical restraints in geriatric care: A systematic review of qualitative and quantitative studies - Möhler, Ralph; Meyer, Gabriele (International journal of nursing studies, 2014)
To examine nurses’ attitudes towards the use of physical restraints in geriatric care. Systematic review and synthesis of qualitative and quantitative studies. The following databases were searched: Medline, CINAHL, EMBASE, Psyndex, PsychInfo, Social SciSearch, SciSearch, Forum Qualitative Social Research (1/1990 to 8/2013). We performed backward and forward citation tracking to all of the included studies. We included in the present review all qualitative and quantitative studies in English and German that investigated nurses’ attitudes towards the use of physical restraints in geriatric care. Two independent reviewers selected the studies for inclusion and assessed the study quality. We performed a thematic synthesis for the qualitative studies and a content analysis of the questionnaires’ items as well as a narrative synthesis for the quantitative surveys. We included 31 publications in the review: 20 quantitative surveys, 10 qualitative and 1 mixed-method study. In the qualitative studies, nurses’ attitudes towards the use of physical restraints in geriatric care were predominately characterised by negative feelings towards the use of restraints; however, the nurses also described a perceived need for using restraints in clinical practice. This discrepancy led to moral conflicts, and nurses described several strategies for coping with these conflicts when restraints were used. When nurses were in doubt regarding the use of restraints, they decided predominantly in favour of using restraints. The results of the quantitative surveys were inconsistent regarding nurses’ feelings towards the use of restraints in geriatric care. Prevention of falls was identified as a primary reason for using restraints. However, the items of the questionnaires focussed primarily on the reasons for the use of restraints rather than on the attitudes of nurses. Despite the lack of evidence regarding the benefits of restraints and the evidence on the adverse effects, nurses often decided in favour of using restraints when in doubt and they used strategies to cope with negative feelings when they used restraints. A clear policy change in geriatric care institutions towards restraint-free care seems to be warranted to change clinical practice. The results of this review should also be considered in the development of interventions aimed at reducing the use of restraints.